Penerapan Aplikasi NASA Power Untuk Perwilayahan Tanaman Kelapa Di Kabupaten Bolaang Mongondow - Nisa, Laila Ainun; Rogi, Johannes Elie Xaveriano; Rombang, Johan Alexander (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
This study aims to assess the climate suitability based on data from the NASA Power application according to the growth requirements of coconut crops in Bolaang Mongondow Regency. The climate parameters analyzed include solar radiation, air temperature, relative humidity, wind speed, and annual rainfall. Data were obtained from the NASA Power application using coordinate points representing coconut-growing areas in 15 subdistricts. The analysis employed a matching approach by comparing the climate parameter values with the coconut crop requirements based on FAO and IAARD criteria. The results showed that all observation areas fall into the S1 (highly suitable) class. Districts such as Lolak and Poigar recorded higher values of radiation and rainfall, supporting optimal plant growth. Climate parameter maps were used descriptively to illustrate variations among regions. This study demonstrates that the NASA Power application can serve as a supporting data source for zoning coconut crops based on climatic suitability.